PENDIDIK PROFESIONAL MENURUT SYEKH AL-USAIMIN - Sopian Sinaga (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The independence of our nation is to educate people's lives so that we become a dignified nation, a just, prosperous and prosperous nation. For this reason, the government and the DPR have enacted the National Education System Law. One of the important elements of education are educators or teachers or lecturers. The success of education is much influenced by the competence and personality of an educator. Therefore, the professionalism of an educator is emphasized in an effort to achieve educational goals. The existence of a figure, namely Sheikh Usaimin, who has proven successful in giving birth to many figures and scholars, is very interesting to discuss how he thinks about professional educators. This research is a qualitative type with a character study approach with a library research method. the information needed was collected from the books of Sheikh al-Usaimin. Analysis of the information obtained was carried out by the method of content analysis. The results of the study show how the principles of an educator and how he behaves and behaves in educating students. Among the principles and attitudes of a professional educator according to Sheikh is that educators must be happy in teaching, love their students, can be role models for them and be sincere, diligent and creative in teaching.